THE EFFECTIVENESS OF MOBILE-ASSISTED LANGUAGE LEARNING IN IMPROVING VOCABULARY AND SPEAKING SKILLS OF JUNIOR HIGH SCHOOL STUDENTS OF SMP AS-SYAKUR SAMPANG - Abd. Sakur; Yudhi Arifani (English Review: Journal of English Education, 2026)
Mobile-Assisted Language Learning (MALL) has shown promise in English language education, yet empirical evidence from rural junior high school contexts remains limited, particularly regarding integrated vocabulary and speaking instruction. This quasi-experimental study investigated the effectiveness of MALL in improving vocabulary and speaking skills among eighth-grade students at SMP AS-Syakur Sampang, Indonesia. Fifty students were divided into experimental (n=25) and control (n=25) groups. The experimental group received six weeks of MALL instruction using WhatsApp, Quizizz, Duolingo, YouTube, and Google Translate, while the control group received conventional instruction. Pre-test and post-test scores were analyzed using independent-sample t-tests. The experimental group significantly outperformed the control group in vocabulary achievement (post-test means: 84.3 vs 71.2; p<0.001) and speaking skills (82.6 vs 70.5; p<0.002). Effect sizes were large (vocabulary d=1.24; speaking d=1.18). Questionnaire results showed high student motivation (4.32) and engagement (4.25). Observations revealed increased student participation and confidence in speaking activities. MALL effectively improves vocabulary mastery and speaking skills in rural junior high school EFL contexts. Mobile applications provide repeated practice, multimodal exposure, collaborative interaction, and flexible learning opportunities that are less available in conventional instruction. Future research should employ longitudinal designs, larger samples, and comparative analyses of specific AI-assisted mobile platforms to further understand technology-mediated language learning effectiveness.